Datação radiocarbônica de sítios arqueológicos do tipo sambaqui pela técnica de absorção de CO2: uma alternativa à síntese benzênica - Mendonça,Maria Lúcia T. G. (2004)
The sambaquis are archaeological sites with remains of pre-historical Brazilian civilizations. They look like small hills containing different kinds of shells, animal and fish bones, small artifacts and even human skeletons. Since the sambaqui sites in the Rio de Janeiro state are younger than 6000 years, the applicability of CO2 absorption on Carbo-Sorb® and 14C determination by counting on a low background liquid scintillation counter was tested. The International Atomic Energy Agency standard reference material IAEA-C2 was used in order to standardize the method. Nine sambaqui samples from five different archaeological sites found in the Rio de Janeiro state were analyzed and 14C ages between 2100 and 3600 years BP were observed. The same samples were sent to the 14C Laboratory of the Centro de Energia Nuclear na Agricultura (CENA/USP) where similar results were obtained.